Evaluation of risk factors of oral cancer - Ekramuddaula, FM; Siddique, BH; Islam, MR; Kabir, MS; Alam, MS (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):412-418 The abstract of this article is available on the PubMed website